"Hug‐an‐orphan vacations": "Love" and emotion in orphanage tourism. Issue 2 (15th June 2017) - Guiney, Tess
Abstract : Experiences involving vulnerable children are among the most popular volunteer tourism practices. Celebrity humanitarianism and aid campaigns promote images of vulnerable children receiving love and care from international celebrities and humanitarian actors (mainly women), normalising intimacy within popular humanitarianism, or "hug‐an‐orphan" vacations – vacations where tourists crave direct contact with children in global South countries (Schimmelpfennig, 2011, http://goodintents.org/orphanages/hug-an-orphan-vacations-3 ). Through accounts given by orphanage directors, volunteers, and commentaries on orphanage tourism, this paper describes the layered emotional entanglements within orphanage tourism. Volunteer tourism literature increasingly recognises the importance of affect in such experiences, principally concentrating on how it leads to its growing popularity. Indeed, many volunteer tourists are motivated from a distance to volunteer at orphanages, being drawn to the possibility of engaging with children. However, their emotions within these encounters are far less examined, and the reality of the lifestyle these children live in is often far more upsetting than expected. Regarding the orphans themselves, the argument I make within this paper is that the commodification of children through orphanage tourism experiences has resulted in an expectation that they will interact with tourists in particular forms. Children are expected to be "poor‐but‐happy" and to engage intimately with volunteers and visitors to engender tourist satisfaction and encourage sympathy and donations. The performance of this behaviour is mediated and controlled by their emotional supervisors, orphanage directors. Through volunteer tourism, children are now a tourist commodity, utilising their love and emotions and creating space for exploitation.